Stress and coping in families - Maguire, Katheryn C. (Cambridge : Polity Press, 2012)
Synthesizes literature from a wide variety of disciplines to examine family interaction in the context of stressful situations. Designed as a textbook within Polity$1 (Bs Key Themes in Family Communication series. Looks at the topic of stress and coping across the individual, relational and family levels.s
pt. 1. Family stress theory and research. Stress in the body and mind -- Stress and the family -- Coping with family stress -- Communication within the stress and coping processes -- pt. 2. Family stress and coping in context. Stress and coping during a wartime deployment -- Stress and coping during catastrophic illness -- Stress and coping during the transition to parenthood.
Includes bibliographical references and index.
Keywords: Stress, Physiological; Family; Communication; Stress (Psychology); Communication in families